Translation Research in the Framework of the Tel Aviv School of Poetics and Semiotics - Weissbrod, Rachel (Meta, 1998)
AbstractIsrael has made an important contribution to translation studies. Since the late 1960s, its contribution in this field is mainly identified with the Tel Aviv school of poetics and semiotics. This paper sets out to introduce the basic ideas of the Tel Aviv school and show how they developed. It surveys the school's achievements in the various branches of translation studies - theory, descriptive research and the applied branches, and examines its impact on translation research in the world. Taking into account some shortcomings which in the author's view might interfere with the school's development, the paper points out the school's future directions of research and the challenges still to be met.